Exhaust Emissions and Combustion Characteristics of a Direct Injection (DI) Diesel Engine Fueled with Methanol-Diesel Fuel Blends at Different Injection Timings - SAYIN, CENK; GÜMÜŞ, METİN (AMER CHEMICAL SOC, 2008)
In the recent years, environmental concerns and depletion in petroleum resources have forced researchers to concentrate on finding renewable alternatives to conventional petroleum fuels. Therefore, alcohols as renewable and alternative energy sources for the diesel engines gain importance. For this reason, in this study, the performance, exhaust emissions, and combustion characteristics of a single cylinder diesel engine have been experimentally investigated under different injection timings when methanol-blended diesel fuel was used from 0 to 15%, with an increment of 5%. The tests were conducted at three different injection timings (15 degrees, 20 degrees, and 25 degrees CA BTDC) by changing the thickness of advance shim. All tests were conducted at four different loads (5, 10, 15, and 20 Nm) at constant engine speed of 2200 rpm. The experimental test results showed that BSFC, BSEC, combustion efficiency, and NOx and CO2 emissions increased as BTE, rate of heat release, peak cylinder pressure, smoke number, and CO and UHC emissions decreased with an increasing amount of methanol in the fuel blend. In comparison to the values at the original injection timing (20 degrees CA BTDC), the values at the retarded injection timing (15 degrees CA BTDC) of peak cylinder pressure, rate of heat release, combustion efficiency, and NOx and CO2 emissions decreased, while smoke number and UHC and CO emissions increased at all test conditions. On the other hand, The advanced injection timing (25 degrees CA BTDC), smoke number, and UHC and CO emissions diminished and peak cylinder pressure, rate of heat release, combustion efficiency, and NOx and CO2 emissions increased at all test conditions. In terms of BSFC, BSEC, and BTE, retarded and advanced injection timings gave negative results in all fuel blends compared to original injection timing.
Keywords: PERFORMANCE; BIODIESEL; ETHANOL; OIL; PARAMETERS